Passive acoustic mapping for monitoring burst wave lithotripsy - Mishra, A (2023)
Burst Wave Lithotripsy (BWL) is a non-invasive treatment modality for kidney stone fragmentation. Studies have shown that BWL induces lesser tissue damage than Shock Wave Lithotripsy and has no risk of infection, as observed in other treatment options such as ureteroscopy. This thesis studied the mechanical properties of porcine tissues and agarose using uniaxial compression testing, oscillatory shear testing and oscillatory nanoindentation testing. This work: i)Investigated the mechanical properties of the kidney at the macro-length scale and micro-length scale. A shear modulus of 0.5 kPa was obtained at 1 Hz, and 0.01% strain using oscillatory shear experiments at the macro-length scale. Oscillatory nanoindentation experiments yielded a shear modulus varying from 25 kPa to 45 kPa as the frequency varied from 10 Hz to 110 Hz at the micro-length scale. ii)Studied other porcine tissues such as the aorta, heart, liver and brain. The highest shear modulus of 4.2 kPa was obtained for porcine aorta, followed by the heart at 1.9 kPa, the liver at 0.3 kPa and the brain at 0.2 kPa. iii)Studied the mechanical properties for a range of agarose concentrations at the macro and micro-length scales, and identified agarose concentrations with viscoelastic properties similar to the porcine organs. The shear modulus of 0.4% agarose resembled the porcine heart, and 0.3% agarose resembled the porcine kidney. The porcine liver had a shear storage modulus 50% lower than the 0.25% agarose, which was the lowest possible agarose concentration for gelation or solidification. At the micro-length scale, the shear modulus of 1.2% agarose was in a similar range as that of the porcine kidney. iv)Applied fractional viscoelastic models to the porcine tissues and agarose samples, and predicted their stress response. The S-FKV model fitted the frequency response of porcine organs, whereas springpot fitted the frequency data of agarose and aorta. The stress predicted for porcine organs and the amplitudes of measurements were within 26% using the S-FKV model and 10% using the springpot model for agarose samples. v) Localised the cavitation events during BWL using Passive Acoustic Mapping (PAM) and quantified the cavitation around the stone using parameters such as the Spatial Integral Frame Power and Treatment Average Total Spatial Power, and investigated the agarose damage. The highest agarose damage and Treatment Average Total Spatial Power were observed in the stones prepared using the rubber mould due to higher surface roughness. Overall this work extracted the mechanical properties of porcine kidneys, which helped us understand their response during the BWL. The mechanical properties of other porcine tissues were extrapolated to higher frequencies using the S-FKV and springpot model and compared with the results from elastography techniques available in the literature. The agarose concentration developed for the porcine heart will be useful as an in-vitro model during elastography, and the agarose concentration developed for the porcine kidney will be helpful as an in-vitro model during lithotripsy. The PAM results showed that cavitation is dominated by the surface roughness and dimensions of stone, which will vary between the patients. We were unable to extract useful time-sensitive information using PAM during the BWL.